2017
DOI: 10.1002/hep.29088
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils promote hepatic metastasis growth through fibroblast growth factor 2–dependent angiogenesis in mice

Abstract: Here, we show, using FGF2 as an example, that identification of factors responsible for the protumoral effects of infiltrating myeloid cells can be used to target established liver metastases. Such therapies could be utilized to limit disease progression and potentiate the effects of standard ablative therapies. (Hepatology 2017;65:1920-1935).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 50 publications
2
92
0
3
Order By: Relevance
“…Therefore, the role of TANs in tumors remains controversial, including CRC 18, 19, 22. Many studies have found neutrophils to be an independent factor of poor prognosis and promote the growth of distance metastases in CRC 23, 24. However, other studies have revealed that tumor‐infiltrating neutrophils are associated with a better prognosis in CRC and might promote antitumor immunity 22, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of TANs in tumors remains controversial, including CRC 18, 19, 22. Many studies have found neutrophils to be an independent factor of poor prognosis and promote the growth of distance metastases in CRC 23, 24. However, other studies have revealed that tumor‐infiltrating neutrophils are associated with a better prognosis in CRC and might promote antitumor immunity 22, 25.…”
Section: Introductionmentioning
confidence: 99%
“…T" [19]. "Metastasis-associated neutrophils expressed substantially more ibroblast growth factor 2 (FGF2) than naïve neutrophils, indicating neutrophil polarization by the tumor microenvironment" [22]. "In control animals changes to the hepatic microenvironment associated with obesity sustained the presence of tumor cells in the liver and increased the incidence of hepatic metastases after intrasplenic/portal inoculation of colon carcinoma cells" [23].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show, using FGF2 as an example, that identi ication of factors responsible for the protumoral effects of in iltrating myeloid cells can be used to target established liver metastases. Such therapies could be utilized to limit disease progression and potentiate the effects of standard ablative therapies" [22].…”
Section: Fusion Hybrid Hypothesis Of Cancer Cell Metastasis Metastatmentioning
confidence: 99%
“…In other contexts, infiltrating neutrophils function to promote cancer progression and metastasis . With respect to liver metastases, neutrophils promote the formation and growth of hepatic metastases from multiple solid cancers …”
mentioning
confidence: 99%
“…Neutrophils positively impact the metastatic process through a variety of functions, including their ability to enhance cancer cell entrapment/seeding within neutrophil extracellular traps, promote cancer cell extravasation, and stimulate angiogenesis . In the context of tumor angiogenesis, there are several mechanisms through which neutrophils play a proangiogenic role.…”
mentioning
confidence: 99%